IMPLEMENTATION OF LEARNING SKILLS SERVICES UNDER VOLLEYBALL STUDENTS OF SMKN 2 KARAWANG - Nurfachrirezi, Aldi; Ismaya, Bambang; Syafei, Muhammad Mury (UNIVERSITAS NEGERI MAKASSAR, 2021)
The purpose of this study was motivated by the students' skills in basic volleyball techniques. This study aims to determine the skills of students in performing under-serviced in class X Accounting SMKN 2 Karawang. This research is a qualitative descriptive study. The population of this study was male and female students of class X Accounting at SMKN 2 Karawang in the 2019/2020 school year, totaling 360 students. The sample of this research was some students of class X Accounting, amounting to 60 students. The data collection techniques used in this study were the results of the students' tests and the results of the observations of the collaborators. Based on research conducted on volleyball service in class X SMKN 2 Karawang both through observations made and interviews conducted on informants, the results showed that the results of learning volleyball under-service volleyball in class X SMKN 2 Karawang were fulfilled from 60 total samples, as many as 59 (98,3%) respondents are in the fulfilled category and the remaining 1 (1,7%) is less fulfilled and there are no respondents who are not fulfilled in the results obtained. Whereas for the results of the analysis of learning to serve under volleyball for class X students of SMKN 2 Karawang which includes 3 aspects, namely preparation, exposure, and final and there are 7 kinds of aspects assessed in the table above shows that the majority of respondents have learning outcomes under volleyball service which are included in the criteria category. Fulfilled as many as 59 (98,3%) of respondents in terms of 3 aspects namely preparation, engagement, and final which is divided into 7 kinds of aspects assessed with an average value obtained by students of 3.0.